Management of 'stress at Job' Among Industrial Workers - Titus, A.P. Sebastian; Jerome, V. Bastin (Ushus Journal of Business Management, 2021)
The paper presents the result of an experimental micro-level study of stress at job. It seeks to examine the stresses affecting the workers and the stress level of workers. It analyses the relationship between stress, job satisfaction, absenteeism and accidents. The data was collected from the workers in mechanical unit of Trichy Steel Rolling Mills (TSRM) Ltd., Trichy in Tamilnadu. The major reasons for 'stress at job' seemed to be inadequacy of salary and the pit falls in work-environment such as non-availability of raw materials on time, waiting for the instructions, unrecognised efforts and services. The workers themselves suggest measures to manage stress at the work place.